The relationship between strategic consensus and entrepreneurial orientation by mediating strategic leadership: An Analytical study in the Directorate for the Protection of Embassies and Diplomatic Missions - Saba Noori Alhamdany,; Sofya Imad Yousif, (Technium Business and Management, 2024)
The objective of this study was to examine the influence of strategic consensus, encompassing dimensions of communication, transparency, and empowerment, on entrepreneurial orientation. Furthermore, it aimed to investigate the role of strategic leadership as a mediating variable in the relationship between strategic consensus and entrepreneurial orientation. The study addressed this issue through various theoretical and practical inquiries formulated based on the current circumstances of Iraqi organizations. The Directorate of Embassy Protection and Diplomats in Baghdad was selected, representing 94% of the total study population. The sample comprised 190 officers, with 170 questionnaires returned after distribution. Following encoding, 20 incomplete questionnaires were excluded, resulting in 160 valid responses. Statistical analysis revealed a significant and meaningful relationship between strategic consensus, strategic leadership, and entrepreneurial orientation, as demonstrated by hypothesis testing.